Post-translational Modifications of the Peptidyl-Prolyl Isomerase Pin1 - Chen, Dongmei; Wang, Long; Lee, Tae Ho (Frontiers in Cell and Developmental Biology, 2020)
The peptidyl-prolyl cis/trans isomerase (PPIase) Pin1 is a unique enzyme that only binds to Ser/Thr-Pro peptide motifs after phosphorylation and regulates the conformational changes of the bond. The Pin1-catalyzed isomerization upon phosphorylation can have profound effects on substrate biological functions, including their activity, stability, assembly, and subcellular localization, affecting its role in intracellular signaling, transcription, and cell cycle progression. The functions of Pin1 are regulated by post-translational modifications (PTMs) in many biological processes, which include phosphorylation, ubiquitination, SUMOylation and oxidation. Phosphorylation of different Pin1 sites regulates Pin1 enzymatic activity, binding ability, localization, and ubiquitination by different kinases under various cellular contexts. Moreover, SUMOylation and oxidation have been shown to downregulate Pin1 activity. Although Pin1 is tightly regulated under physiological conditions, deregulation of Pin1 PTMs contributes to the development of human diseases including cancer and Alzheimer’s disease (AD). Therefore, manipulating the PTMs of Pin1 may be a promising therapeutic option for treating various human diseases. In this review, we focus on the molecular mechanisms of Pin1 regulation by PTMs and the major impact of Pin1 PTMs on the progression of cancer and AD.